Social research methods : - Neuman, William Lawrence (Pearson/AandB, 2006)
This highly regarded text presents a comprehensive and balanced introduction to both qualitative and quantitative approaches to social research, emphasizing the benefits of combining various approaches. Dozens of new examples from actual research studies help illustrate concepts and methods.